Immune imbalance in the human hippocampus in PTSD revealed by single-nucleus transcriptomics - Liu, Liu; Li, Pengfei; Wilkerson, Brent A.; Wu, Yan; Liu, Meng; Shi, Roger; Hamlett, Eric D.; Carroll, Steven L.; LaRue, Amanda C.; Wang, Zhewu; Fan, Hongkuan (Frontiers in Immunology, 2026)
IntroductionPost-traumatic stress disorder (PTSD) is increasingly recognized as a neuroimmune disorder in which disrupted neuron–glia interactions contribute to long-term cognitive and emotional dysfunction. However, the cellular and molecular basis of immune imbalance in the human hippocampus remains unclear.MethodsWe performed single-nucleus RNA sequencing on postmortem hippocampal tissues from donors with PTSD and matched controls, identifying 10 major cell types, with particular emphasis on neurovascular and glial populations. Differential expression, pathway enrichment, pseudotime trajectory, and cell–cell communication analyses were applied to characterize cellular and molecular alterations.ResultsPTSD samples showed prominent activation of stress-response and inflammatory signaling across astrocytes, microglia, endothelial cells, and mural cells. Microglia and astrocytes underwent robust transcriptional reprogramming with enrichment of immune-related pathways, while endothelial and mural cells exhibited inflammation and impaired blood–brain barrier homeostasis. Trajectory analyses revealed altered state transitions in astrocytes and microglia, indicating dysregulated responses to stress. Furthermore, cell–cell communication analysis uncovered markedly reduced interactions between astrocytes or microglia with excitatory neurons and oligodendrocyte lineage cells, particularly involving stress- and inflammation-related ligand–receptor pairs.DiscussionThese findings demonstrate that PTSD is characterized by immune imbalance at both cellular and intercellular levels, driven by maladaptive glial activation and disrupted neuron–glia communication. Our study provides a comprehensive single-cell atlas of the hippocampal neuroimmune landscape in PTSD and highlights dysfunctional glial–neuronal interactions as a central mechanism underlying disease pathogenesis.